Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes - Lima, Daniel; Tavares, Marcos; de Mendonça, Joel Braga Jr. (Zootaxa, 2019)
Trindade and Martin Vaz (TMV) is a highly isolated, oceanic volcanic archipelago located some 1200 km off the Brazilian coast and about 4200 km away from the nearest African coast. For almost 100 years Calcinus tibicen (Herbst, 1791) was the only hermit crab species known from TMV. From 2012 to 2018, 263 daytime SCUBA diving and intertidal samplings conducted at TMV yielded 1075 paguroid specimens in 10 species, three of which are established herein as new species: Iridopagurus martinvaz sp. nov., Nematopagurus micheleae sp. nov., and Pagurus carmineus sp. nov. Iridopagurus margaritensis García-Gómez, 1983, and Phimochirus leurocarpus McLaughlin, 1981, both only known from the northern hemisphere, are recorded for the first time from the southwestern Atlantic. Opportunity was taken herein to include hitherto unreported or little known specimens from along the Vitória-Trindade Seamount Chain, namely, Dardanus venosus H. Milne Edwards, 1848, Nematopaguroides pusillus Forest & de Saint Laurent, 1968, Pagurus provenzanoi Forest & de Saint Laurent, 1968, and Phimochirus holthuisi (Provenzano, 1961). The lectotype of Pagurus venosus H. Milne Edwards, 1848 is designated as the neotype for the obscure Pagurus arrosor divergens Moreira, 1905, which thus becomes an objective junior synonym of the former. A list of all paguroid species known from the tropical southern-central Atlantic oceanic archipelagoes and islands (Ascension, Cape Verde, Fernando de Noronha, Gulf of Guinea, Rocas Atoll, Saint Helena, Trindade and Martin Vaz) with their gross distribution in the Atlantic Ocean is provided. Investigation on the existence of patterns of geographic distribution for the paguroid fauna of the tropical southern-central Atlantic oceanic islands showed that 70% percent of the paguroids from TMV are western Atlantic in origin and 30% endemic. No amphi-Atlantic paguroid species are known from TMV. Conversely, the affinity of Ascension’s (33%) and Saint Helena’s (50%) paguroids is with the eastern Atlantic; no western Atlantic paguroids have been reported from these two islands so far. Exploration on the existence of trends of correlation between islands area and species richness through the Spearman’s coefficient of correlation showed that the patterns in the number of paguroid species cannot be explained by variation in island area alone (rs = 0.4728; p = 0.28571).